2015
DOI: 10.1158/1538-7445.am2015-2596
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 2596: ACP-196: a novel covalent Bruton's tyrosine kinase (Btk) inhibitor with improved selectivity and in vivo target coverage in chronic lymphocytic leukemia (CLL) patients

Abstract: Ibrutinib, a first generation Btk inhibitor, is approved for the treatment of CLL and mantle cell lymphoma; known toxicities include atrial fibrillation, diarrhea, rash, arthralgia and bleeding events (1). Recent reports show ibrutinib's off target effects may negatively impact its potential for combined therapy with anti-CD20 antibodies (2,3). Here we describe the pharmacologic characterization of ACP-196 a potent, novel second generation Btk inhibitor, which binds covalently to Cys481 with improved selectivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 0 publications
1
30
0
2
Order By: Relevance
“…Differential effect of these two drugs on T-cells was further evidenced in Jurkat T-lymphoblastic cell line for ITK and PLCγ1 (Figure 6C-E). Consistent with these data, previous studies with acalabrutinib demonstrated minimal effects on EGFR, Tec, or ITK signaling, and no inhibition of thrombus formation in vivo at clinically relevant concentrations (32,51). …”
Section: Discussionsupporting
confidence: 85%
“…Differential effect of these two drugs on T-cells was further evidenced in Jurkat T-lymphoblastic cell line for ITK and PLCγ1 (Figure 6C-E). Consistent with these data, previous studies with acalabrutinib demonstrated minimal effects on EGFR, Tec, or ITK signaling, and no inhibition of thrombus formation in vivo at clinically relevant concentrations (32,51). …”
Section: Discussionsupporting
confidence: 85%
“…7 Acalabrutinib was developed as a selective BTK inhibitor when compared to ibrutinib with the goal of achieving similar therapeutic outcomes in patients with CLL without the off-target effects on other kinases such as TEC, EGFR, and ITK. [7][8][9] Several pre-clinical studies have demonstrated the efficacy of acalabrutinib inhibition of BTK is similar to that seen with ibrutinib. These findings led to a phase 1/2 study to evaluate the efficacy and side-effect profile of acalabrutinib in CLL.…”
Section: Development Of Acalabrutinibmentioning
confidence: 91%
“…2,17,18 Acalabrutinib, a second generation, irreversible BTK inhibitor, was developed as a selective BTK inhibitor to avoid the off-target side effects seen ibrutinib. [7][8][9] Zanubrutinib, a next-generation, irreversible BTK inhibitor, was developed as a selective BTK inhibitor and has received approval for treatment of relapsed refractory mantle cell lymphoma. 19 Studies are ongoing in evaluating the drug's safety and efficacy in CLL.…”
Section: Role Of Bruton's Tyrosine Kinase Inhibitors In Cllmentioning
confidence: 99%
See 1 more Smart Citation
“…However, ibrutinib has untoward effects, such as bleeding, rash, and atrial fibrillation, which could be partly due to the bystander effects on targets other than BTK [ 10 , 13 , 15 , 17 , 18 ]. Therefore, more selective BTK inhibitors (ACP-196, ONO/GS-4059, BGB-3111, CC-292) are being explored [ 19 23 ]. Acalabrutinib, also known as ACP-196, is a novel irreversible second-generation BTK inhibitor that was rationally designed to be more potent and selective than ibrutinib [ 19 , 24 28 ].…”
Section: Introductionmentioning
confidence: 99%